THE ZONALITY OF ILMENITE BATTERIES WITHIN THE BOUNDARIES OF THE IRSHAN BATTLE FIELD OF THE UKRAINIAN SHIELD - Komliev, О. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
World-class titanium and titanium-zirconium placer deposits are located on the territory of Ukraine. They form Ukrainian sub-province of the placer province of Eastern Europe. It also includes the Irshansky placer field for the development of short-lived ilmenite placers. The article presents the results of research of the spatial ratio of placers and root sources, vertical and horizontal zonation of the material composition of placers on 9 detailed sections. This allows us to identify additional criteria for establishing the genesis of placers, which is important when conducting paleogeographic and paleogeomorphological work. The main sources of placers were mainly stratum bodies of various thicknesses, which were independent structures or were elements of the now destroyed domed structures of the foundation. The indigenous bodies and placers in the plan coincide completely, partially, or do not coincide. The criterion of coincidence of root and placer bodies indicates that the useful component from the root bodies to placers moved a distance of several hundred meters. Loose deposits contained in the sediments of the Poltava suite formation of the Late oligocene-Middle miocene age were eluvial, eluvial-deluvial, deluvial, deluvial-alluvial, proluvial and alluvial by genesis. Paleorelief was then favorable for the preservation of placers as the primary concentrations of the useful component of indigenous sources, and their enrichment. Ilmenite placers were then formed on all hypsometric levels of ancient relief, but the most significant of them are at the lower level (in the bottoms and on the slopes of ancient valleys). The results of analyzes of granulometric and chemical composition of monofraction of ilmenite placers, granulometric and material composition of sediment-containing placers, were studied in combination with other data (structural-tectonic, paleogeomorphological).Analyses of the material composition of placers and sediments were selected by interval testing of sections. Based on the results of their processing, quantitative indicators characterizing the particle size distribution and chemical composition of ilmenite were calculated. Their study made it possible to identify different types of sections in the deposits of the contribution of the Poltava suite formation (8 – according to granulometry, 10 – according to the change in the chemical composition of ilmenite), vertical and horizontal zonality, allowing solving various problems (paleogeomorphological reconstructions, to identify consedimentary structures, location detection tectonic inversions).
Keywords: ilmenite; іlmenite placers; root springs; zonation of placers; paleorelief